AGEs, contributors to placental bed vascular changes leading to preeclampsia. (August 2013) - Guedes-Martins, L.; Matos, L.; Soares, A.; Silva, E.; Almeida, H.
Abstract Glycation of proteins or other biomolecules and their further long-term degradation result in the formation of advanced glycation end products, AGEs. AGEs and other ligands interact with their receptors, RAGEs, localized to a variety of tissues, but mainly in endothelium and vascular wall cells. This interaction triggers diverse signaling pathways that converge on the activation of NF-κB and the initiation of a local inflammatory reaction that, when prolonged, results in dysfunctional features. Preeclampsia is a serious vascular disorder centred at the placenta–uterine interface, the placental bed, but the condition extends to the mother´s circulation. RAGEs have notorious expression in the placental bed tissues along pregnancy but, in addition, RAGEs and their ligands are expressed in the fetal membranes and are found in the amniotic fluid and the mother´s serum. Disorders complicating pregnancies and having an important vascular involvement, as preeclampsia and diabetes mellitus, have additional enhanced AGE/RAGE expression variation. This indicates that for their assessment, the assay of RAGEs or their ligands may become useful diagnostic or prognostic procedures.